يوغرطة في حربه ضد روما 112 ق م – 104 ق م - عبد الحميد عمران (My University, 2017)
الملخص لملخص: يرى الكاتب الروماني سالبسةيوم بكن يوغرطة لى يمر راضيا ع مر ت سيى المملمة النوميدية، لمنه تظاهر بال بول والرض لكي لا يواجه الرومان عسمربا، ول ب الوقت وبنظى مره وتتوضي لديه لأمور .. وبعد موت العاهل ماسيتسا تممر مر ال يام بغارة خاطفة ع ذربعل ممنته مر الحصول ع المن مر الغنائى.. مما د بكذربعل إل ت ديى شكاية إل روما عر يوديدات يوغرطة. الد اان قد حامر العاممة س تا لمدة ش ر وهدد مصالي روما، خصوما بعد تد ن العديد مر الوخصيات الرومانية البارزة إل المدينة قبل ذلك، كما ن الامتيازات التي منح ا الملك مسيتسا للرومان مارت م ددة.. وم شل اللجان الرومانية المرسلة إل س تا عاد يوغرطة حصار المدينة والاسةي عل وا عام 112 ق م. مما د بالجالية الرومانية إل إيارة الف ن ب ن ورية العرش النوميد وإعطا ذريعة التدخل العسمر الروماني.. Summary The writer Sallust that Jugurtha was not satisfied with the division of the Numidia kingdom ordered but he showed acceptance and satisfaction in order to move away from the face of the Roman army, and save time and effort, organize his command and smoke has things. Jugurtha shares the throne of Numidia with the two sons of the king, Hiempsal and Adherbal. He did however assassinate the first and attacked the second, who fled to Rome to ask for help, no change of monarch could not be done without the approval of the Senate. يوغرطة في حربه ضد روما 112 ق م- 104 ق م د. عمران عبد الحميد 354 - مجلة العلوم الاجتماعية والإنسانية - العدد: 13 - ديسمبر 2017 - The latter decides to divide Numidia between Adherbal, who obtains the eastern half, prosperous, and Jugurtha, which receives the western part, little developed. Confident in his influence in Rome, Jugurtha again attacked Adherbal in 112 BC. BC and killed him after seizing his capital, Cirta. During the siege of this city, many Italian merchants were massacred. And managed to make a raid glance at Adherbal allowed him to get plenty of booty. Encouraging Adherbal to file a complaint in Rome for threats Jugurtha. Who besieged the capital, Cirta for months ,, making the interests of Rome threatened, especially after the influx of many Romanian dignitaries to the city before, and that the privileges granted to them by King Micipsa become threatened. Committees Romania However sent failed to Cirta restored Jugurtha seat Cirta and catch them in 112 av / jc .. inciting the Romanian diaspora to stir up the sedition between the heirs of the Numidia throne and give a pretext for Roman military intervention